Identifying Constraints to Financial Inclusion and Their Impact on GDP and Inequality. - Dabla-Norris, Era (IMF Working Papers., 2015)
We develop a micro-founded general equilibrium model with heterogeneous agents to identify pertinentconstraints to financial inclusion. We evaluate quantitatively the policy impacts of relaxing each of theseconstraints separately, and in combination, on GDP and inequality. We focus on three dimensions of financialinclusion: access (determined by the size of participation costs), depth (determined by the size of collateralconstraints resulting from limited commitment), and intermediation efficiency (determined by the size ofinterest rate spreads and default possibilities due to costly monitorin.